Management Inventory Produk Cat Menggunakan Metode Safety Stock dan Reorder Point Pada TB Gamping Pilihan Sukoharjo - Edenniera Zefanya Christyani; Ari Susanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to address inventory and demand fluctuations at TB Gamping Pilihan Sukoharjo through the application of Safety Stock and Reorder Point methods. Efficient inventory management is crucial for both manufacturing and trading companies to deal with market demand uncertainties and maintain operational stability. This research uses a descriptive qualitative method, with data collection techniques including in-depth interviews, document studies, and observation. The results show that the Safety Stock method helps the company anticipate stock shortages caused by supply chain disruptions or unexpected demand surges. Meanwhile, Reorder Point is used to determine the optimal time for reordering to prevent stockouts. Inventory calculations were tested using Microsoft Excel on 10 sample data items, showing that the inventory management system at TB Gamping Pilihan Sukoharjo operates accurately, with consistent Safety Stock and Reorder Point calculations. This study concludes that the application of these two methods can improve the efficiency of inventory management in the company